2017
DOI: 10.1002/mar.21049
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing user sentiment in social media: Implications for online marketing strategy

Abstract: This article examines restaurant customers’ online activity following visits to restaurants. Differences in customers’ opinions based on gender and location are discussed. Sentiment analysis was used to analyze customers’ social media behavior in terms of liking, rating, and reviewing restaurants. User‐generated reviews and comments about experiences influence potential customers’ decisions. The results of this study show that gender and location of customers influence restaurant ratings. This article shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 28 publications
1
38
0
3
Order By: Relevance
“…As mentioned previously, event outcomes refer to the observed firm performance during customers’ brand- or firm-related interactions. We focus on individuals’ experiential interactions with a firm or brand, consistent with research on service encounters (Micu et al 2017), and postconsumption product perceptions (Babić Rosario et al 2016). While overall satisfaction (Farhadloo, Patterson, and Rolland 2016; He et al 2016; Misopoulos et al 2014) and brand perceptions (Schweidel and Moe 2014) reflect customers’ experiences, these concepts are often broader, reflecting a series of interactions or experiences.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…As mentioned previously, event outcomes refer to the observed firm performance during customers’ brand- or firm-related interactions. We focus on individuals’ experiential interactions with a firm or brand, consistent with research on service encounters (Micu et al 2017), and postconsumption product perceptions (Babić Rosario et al 2016). While overall satisfaction (Farhadloo, Patterson, and Rolland 2016; He et al 2016; Misopoulos et al 2014) and brand perceptions (Schweidel and Moe 2014) reflect customers’ experiences, these concepts are often broader, reflecting a series of interactions or experiences.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…particular topic such as a brand, or organization. For example, Micu et al (2017) discuss the use of sentiment analysis in understanding the valence of social media posts and its role in the development of online marketing strategy.…”
Section: The Search Terms Definedmentioning
confidence: 99%
“…Sentiment analysis refers to the process of using a computer to identify and categorize the tone expressed in a piece of text, usually to determine the valence of the author’s attitude towards a particular topic such as a brand, or organization. For example, Micu et al (2017) discuss the use of sentiment analysis in understanding the valence of social media posts and its role in the development of online marketing strategy.…”
Section: The Search Terms Definedmentioning
confidence: 99%
“…TextBlob is a Python (2 and 3) library for processing textual data. Micu et al [46] employed TextBlob to analyze customers' liking, rating and reviewing restaurants. They found that TextBlob is an effective tool sentiment analysis tool.…”
Section: Sentiment Analysismentioning
confidence: 99%